How functional genomics will impact fruit fly pest control: the example of the Mediterranean fruit fly, Ceratitis capitata - Scolari, Francesca (BMC Genet, 2014)
The highly invasive agricultural insect pest Ceratitis capitata (Diptera: Tephritidae) is the most thoroughly studied tephritid fruit fly at the genetic and molecular levels. It has become a model for the analysis of fruit fly invasions and for the development of area-wide integrated pest management (AW-IPM) programmes based on the environmentally-friendly Sterile Insect Technique (SIT). Extensive transcriptome resources and the recently released genome sequence are making it possible to unravel several aspects of the medfly reproductive biology and behaviour, opening new opportunities for comparative genomics and barcoding for species identification. New genes, promotors and regulatory sequences are becoming available for the development/improvement of highly competitive sexing strains, for the monitoring of sterile males released in the field and for determining the mating status of wild females. The tools developed in this species have been transferred to other tephritids that are also the subject of SIT programmes.